CARBON SEQUESTRATION FOR AGROSILVICULTURE AGROFORESTRY PRACTICES: PRELIMINARY RESULTS FROM THREE INVESTIGATED VILLAGES IN UTTARADIT PROVINCE, NORTHERN, THAILAND - Chattanong Podong; Krissana Khamfong; Supawadee Noinamsai; Sukanya Mhon-ing (BIOTROPIA, 2024)
ARTICLE HIGLIGHTS- Agroforestry boosts carbon storage, reducing greenhouse gas emissions significantly.- Diverse tree-based farming enhances biodiversity, soil health, and climate resilience.- Carbon sequestration in agroforestry supports sustainable agriculture and environmental balance.- Agroforestry practices mitigate climate change by storing carbon in trees and soil.- Combining trees with crops provides multiple ecological and economic benefits.ABSTRACTOne of the processes for compensating greenhouse gas emissions is atmospheric carbon removal and storage in the terrestrial biosphere. Agricultural systems to which trees are returned for careful management alongside crops and animals are thought to be substantial CO2 sinks. People are increasingly realizing the importance of agroforestry because it is good for the environment and farming. In this study, total carbon pools from the aboveground biomass carbon (ABGC), forest floor carbon (FFC), and soil organic carbon (SOC) were investigated and carbon storage data for some agroforestry practices native to Uttaradit in northern Thailand were analyzed. The role of these carbon pools in reducing CO2 concentrations in the atmosphere was also discussed. The results showed differences in the total carbon stock sourced from traditional agroforestry (TAF), applied agroforestry (AAF), and developed agroforestry (DAF). The total carbon store (ABGC + TFFC + SOC) of TAF, AAF, and DAF was 267.05 Mg C/ha, 226.48 Mg C/ha, and 324.70 Mg C/ha, respectively. SOC contributed 47.64%, 54.26%, and 44.81% and ABGC contributed 22.75%, 19.79%, and 23.90% to the total carbon stock in TAF, AAF, and DAF, respectively. The CO2 adsorption was 979.27 Mg CO2/ha, 830.50 Mg CO2/ha, and 1,190.6 Mg CO2/ha in TAF, AAF, and DAF, respectively. It is clear that agroforestry systems serve as carbon sinks in terrestrial ecosystems. Although the comparison of agroforestry practices and other land use types is important for carbon mitigation and the implementation of the “Land Use, Land Use Change, and Forestry” concept for CO2 sinks, it is also crucial to compare the potential of carbon sequestration in different CO2 pools.